2023
DOI: 10.1126/scitranslmed.adf3309
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human germline-targeting HIV nanoparticle vaccine induced broad and publicly targeted helper T cell responses

Abstract: The engineered outer domain germline targeting version 8 (eOD-GT8) 60-mer nanoparticle was designed to prime VRC01-class HIV-specific B cells that would need to be matured, through additional heterologous immunizations, into B cells that are able to produce broadly neutralizing antibodies. CD4 T cell help will be critical for the development of such high-affinity neutralizing antibody responses. Thus, we assessed the induction and epitope specificities of the vaccine-specific T cells from the IAVI G001 phase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Burton discussed an engineered nanoparticle vaccine immunogen referred to as eOD-GT8 60 mer, which was developed by scientists at Scripps Research, Fred Hutchinson Cancer Center (through the HIV Vaccine Trial Network, HVTN), NIAID, and IAVI and tested in Phase 1 clinical trials. The vast majority of vaccinees (97%) showed VRC-01-class bNAb precursors with a median frequency of 0.1% IgG + B cells in blood, indicating that reverse immunogen engineering can stimulate and expand rare germline B cells 11 , 12 .…”
Section: The Landscape Of B Cell-targeted Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Burton discussed an engineered nanoparticle vaccine immunogen referred to as eOD-GT8 60 mer, which was developed by scientists at Scripps Research, Fred Hutchinson Cancer Center (through the HIV Vaccine Trial Network, HVTN), NIAID, and IAVI and tested in Phase 1 clinical trials. The vast majority of vaccinees (97%) showed VRC-01-class bNAb precursors with a median frequency of 0.1% IgG + B cells in blood, indicating that reverse immunogen engineering can stimulate and expand rare germline B cells 11 , 12 .…”
Section: The Landscape Of B Cell-targeted Vaccinesmentioning
confidence: 99%
“…Researchers are also testing the eOD-GT8 immunogen expressed from mRNA encapsulated in lipid nanoparticles (IAVI G002, NCT05001373), and, according to Burton, this approach appears even more promising than the equivalent nanoparticle protein previously tested 12 . The goal now is to continue this work and to test eOD-GT8 and other germline-targeting immunogens singly and in combination with more native-like stabilized HIV envelope trimers.…”
Section: The Landscape Of B Cell-targeted Vaccinesmentioning
confidence: 99%
“…In fact, several combination vaccine candidates against seasonal respiratory diseases utilizing next-generation vaccine platforms (e.g., Flu-COVID, Flu-RSV, and Flu-COVID-RSV) are currently being tested in Phase 2/3 clinical programs and vaccines with multiple strains of the same virus are already available to the public (e.g., FluMist Quadrivalent) [ 60 , 63 ]. mRNA-based vaccine development has even opened the doors to targeting diseases caused by latent viruses (e.g., cytomegalovirus [CMV] and human immunodeficiency virus [HIV]), enteric viruses (e.g., noroviruses), and bacteria (e.g., Lyme disease) [ 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Improved Ability To Develop Combination Vaccinesmentioning
confidence: 99%
“…Nanotechnology offers insights into protein-based NP properties that are crucial for strong immunity and can help fight against infectious diseases. Both chemical conjugation and genetic fusion are useful methods for loading antigens onto scaffolds, and increasing numbers of studies have shown that both strategies are advantageous for immunogen design. , …”
Section: Vaccines Contribute To Long-lasting Immunitymentioning
confidence: 99%
“…Both chemical conjugation and genetic fusion are useful methods for loading antigens onto scaffolds, and increasing numbers of studies have shown that both strategies are advantageous for immunogen design. 135,136 Nonprotein Immunogens Can Enable Long-Lasting Immunity. Due to their high surface energy, multiple functional chemical groups, and special interface characteristics, nanomaterials possess large capacity for biomolecule adsorption.…”
Section: Vaccines Contribute To Long-lasting Immunitymentioning
confidence: 99%